A new species of the genus Livistona R. Br. (Arecaceae Schltz-Sch.) for the flora of Vietnam - Phuong Anh, Tran Thi (Academia Journal of Biology, 2014)
A new species of the genus Livistona R. Br. (Arecaceae Schltz-Sch.) for the flora of Vietnam